P232 Bowel cancer screening programme; designed for an asymptomatic population, but is this the case?. (19th June 2022) - Granville, Rosie; Baldwin, Tania; Serna, Solange; Verma, Ajay
Abstract : Introduction: Bowel Cancer Screening Programme (BCSP) was designed to screen an asymptomatic middle-aged population for pre-malignant colonic adenomas and early colorectal cancer (CRC). Whilst the programme is considered a success, ~40% of those diagnosed with CRC are still having adverse outcomes with advanced disease which is non-curable. 1 When informing patients of a CRC diagnosis at colonoscopy, it is not uncommon to hear that they have had suggestive symptoms for many months. We aim to evaluate the proportion of patients diagnosed with CRC at BCSP, who have suggestive symptoms. Methods: Data from the Exeter reporting database on symptoms recorded by the specialist screening practitioners at pre-endoscopy assessments for patients diagnosed with CRC were analysed. Symptoms were classified as red flag (based on urgent cancer pathway referral criteria); change in bowel habit, rectal bleeding, weight loss, abdominal pain, and other ; chronic diarrhoea, constipation, mucous discharge, urgency of defecation, rectal irritation. Results: Data were analysed on symptoms recorded pre-endoscopy from 316 patients diagnosed with CRC in BCSP 2015-2021 (7 years) in the Northamptonshire BCSP. 1) 180 males (57.0%)/132 female (41.8%)/4 unrecorded (1.3%) Mean/median age = 68.0/68.7 years 69 patients were asymptomatic (21.8%) 247 patients were symptomatic (78.2%), HR 3.58 (95% CI 2.63–4.88; p <0.0001) 166 had red flag symptoms (52.5%), HR 2.41 (95% CI 1.75–3.32; p <0.0001) The most common reported symptom reported by patients was urgency of defecation (49.9%) The most common reported red flag symptom was change in bowel habit (45.8%) Conclusions: This analysis significantly shows that the vast majority of patients diagnosed with CRC in BCSP were symptomatic, with over half having red flag symptoms. Those patients should have ideally been managed on symptomatic pathways (especially those with red flag symptoms) in a timely manner. Despite the BCSP being aimed at an asymptomatic population, it is possibly acting as a safety net for those with suggestive symptoms for weeks or months. It is sobering to contemplate that without a BSCP colonoscopy diagnosing CRC, some of these patients may have presented later as an emergency with a severe complication such as bowel obstruction or metastatic disease. The population awareness about symptoms of CRC, and the effectiveness of symptomatic pathways in identifying symptoms and managing patients with CRC needs to improve. Reference: Verma A, Chilton A PTU-067 The positive impact of the bowel cancer screening programme on colorectal cancer diagnoses and outcomes Gut 2018;67:A204-A205.